Bacterial Genetic Approach to the Study of Reactive Oxygen Species Production in Galleria mellonella During Salmonella Infection - Bismuth, Hanna D.; Brasseur, Gaël; Ezraty, Benjamin; Aussel, Laurent (Frontiers in Cellular and Infection Microbiology, 2021)
Over the last decade, an increasing number of reports presented Galleria mellonella larvae as an important model to study host-pathogen interactions. Coherently, increasing information became available about molecular mechanisms used by this host to cope with microbial infections but few of them dealt with oxidative stress. In this work, we addressed the role of reactive oxygen species (ROS) produced by the immune system of G. mellonella to resist against Salmonella enterica, an intracellular pathogen responsible for a wide range of infections. We confirmed that Salmonella was pathogen for G. mellonella and showed that it had to reach a minimal bacterial load within the hemolymph to kill the larvae. ROS production by G. mellonella was revealed by the virulence defects of Salmonella mutants lacking catalases/peroxiredoxins or cytoplasmic superoxide dismutases, both strains being highly sensitive to these oxidants. Finally, we used bacterial transcriptional fusions to demonstrate that hydrogen peroxide (H2O2) was produced in the hemolymph of Galleria during infection and sensed by S. enterica. In line with this observation, the H2O2-dependent regulator OxyR was found to be required for bacterial virulence in the larvae. These results led us to conclude that ROS production is an important mechanism used by G. mellonella to counteract bacterial infections and validate this host as a relevant model to study host-pathogen interactions.